Advanced separation techniques for biodiesel production from transesterification process - Mohd Amir Idhzuan Johari (School of Bioprocess Engineering, University Malaysia Perlis, 2011)
Once biodiesel produced, it contains several impurities such as soap and glycerol. The free fatty acids (FFA) in the oil react with the sodium or potassium catalyst to form soaps. After the biodiesel and by product glycerol are separated, trace amounts of glycerol remain in the biodiesel. Recently, there are wet and dry wash separation procedures have been used, such as hot distilled water, activated carbon and silica gel blue to remove those by-product. The objective of this study was to determine the highest yield conversion of biodiesel from the significant parameters (methanol-to-oil molar ratio and reaction temperature). Second objective was to compare these dry and wet wash (hot distilled water) methods by their mode of operation and effectiveness. Results indicate that the highest conversion of biodiesel production can be achieved with optimized reaction conditions through Design Expert software; Response Surface Method: Central Composite Design (RSM: CCD) where this software can determine the best and optimum conditions from the study parameters. The optimized reaction condition for producing biodiesel; methanol-to-oil molar ratio is 12:1 ratio and reaction temperature of transesterification process is 59.21 C (60 C) with the yield conversion of biodiesel is 83.89 % from raw material of refined, bleached and deodorized palm olein (RBDPO). Beside that, silica gel blue can reduce soap and glycerol efficiently compared to washing with activated carbon and hot distilled water. This statement based on the qualitative analysis of the Fourier Transform Infrared (FTIR) spectroscopy and gas chromatography (GC) with the purity of treated biodiesel washed with silica gel blue was 69.18 %. Thus, both of the objectives was achieved and determined in order to produce efficient biodiesel.